Sintesis Karbon Aktif dari Kulit Salak dengan Aktivasi H3PO4 sebagai Adsorben Larutan Zat Warna Metilen Biru - Maria Angela NS (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Activated carbons have been prepared from salacca peels by chemical activation with phosphoric acid (H3PO4). Salacca peels were firstly impregnated at a fixed salacca peel to phosphoric acid ratio of 1:4 and fixed phosphoric acid concentration of 20 %-w. The impregnated salacca peel were then carbonized in an electrical furnace at temperature of 600 °C in inert condition. Macroporous activated carbons with a high surface area of 691,59 m2/g were obtained. The produced activated carbon the is taken for about 0,025 g to adsorb methylene blue (MB) from 250 mL of aqueous phase with various initial concentration of 10, 20, 30, 40, and 50 ppm. Based on the adsorption of dye, it can be concluded that the adsorption of the MB obeys the Langmuir adsorption isotherm, with adsorption capacity of 256,41 mg solute/ g activated carbon. Based adsorption studies, based on the assumption of a pseudo-first-order, pseudo-second-order or intraparticle diffusion mechanism, showed that the kinetic data followed closely a pseudo-second-order rather than a pseudo-first-order mechanism. Experimental results showed that salacca peels seems to be an alternative precursor for commercial activated carbon.